Relationship between somatotype components and muscle fiber type - Fahri S. Çınarlı (Physical Education of Students, 2021)
Background and Study Aim. It is stated that genetic factors, lifestyle and demographic components affect the morphological properties of the muscle; moreover, there is a relationship between adiposity indicators and skeletal muscle. The aim of this study is to examine the relationship between the somatotype components and obesity markers and the percentage of the fast twitch fibril type of skeletal muscle.